2012
DOI: 10.1016/j.mayocp.2012.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The Elders Risk Assessment Index, an Electronic Administrative Database–Derived Frailty Index, Can Identify Risk of Hip Fracture in a Cohort of Community-Dwelling Adults

Abstract: Objective: To determine whether an Elders Risk Assessment (ERA) index can predict incident hip fractures without the need for physician-patient encounter or bone mineral density testing. Patients and Methods: A retrospective cohort study was conducted in a community-based cohort of 12,650 patients aged 60 years and older. An ERA score was computed for each subject at index time (January 1, 2005). Incidents of hip fracture from January 1, 2005, through December 31, 2006, were obtained from electronic medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
(34 reference statements)
2
10
0
Order By: Relevance
“…Previous studies investigating the relationship between a FI and fractures reported significant results [23][24][25][26], which was in line with our findings. For example, the Canadian Multicentre Osteoporosis Study (CaMos) using a 30-item FI to predict 10-year fracture risk reported significant associations between the FI and fractures in adults, with a HR of 1.18 for hip fracture and 1.30 for clinical vertebral fractures (pvalues b 0.05) for per-0.10 increase in FI [26].…”
Section: Comparison With Other Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies investigating the relationship between a FI and fractures reported significant results [23][24][25][26], which was in line with our findings. For example, the Canadian Multicentre Osteoporosis Study (CaMos) using a 30-item FI to predict 10-year fracture risk reported significant associations between the FI and fractures in adults, with a HR of 1.18 for hip fracture and 1.30 for clinical vertebral fractures (pvalues b 0.05) for per-0.10 increase in FI [26].…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…The FI could grade and predict the risk of fractures based on the degree of frailty in the elderly, which had been explored in previous studies [23][24][25][26]. However, limited evidence comparing the predictive accuracy of the FI and FRAX in the risk of fractures is available.…”
Section: Introductionmentioning
confidence: 99%
“… 6 To investigate a possible effect on hospital admissions or emergency visits in patients with several chronic (including respiratory) conditions, an individually randomised controlled trial was performed in the United States, comparing daily telemonitoring (including biometry, symptom registration and video consultation by Internet) with usual care during 1 year. This well-conducted study among 205 elderly people with multi-morbidity (defined as a Charlson Comorbidity Index 7 >2.9) and a high risk for hospitalisation (a score >15 on the Elder risk assessment index) 8 did not result in significant benefit of the intervention. No statistically relevant difference was found between the intervention group of patients (63.7%) and the control group (57.3%) in the number of hospitalisations or emergency visits ( P =0.35).…”
Section: Illustrative Experiences In High-income Settingsmentioning
confidence: 94%
“…It has been validated as a predictor for hip fractures [18], and to predict mortality and Aged Care placement in community-dwelling adults [19]. An Elders Risk Assessment Index of 16 or more has also been hypothesised in the literature as a measuring instrument to select patients for referral to a transitional care programme for community dwelling adults [20].…”
Section: Introductionmentioning
confidence: 99%